Inability of Polysaccharides of Spirulina Platensis to Protect Hepatocyte Cells Line on Toxoplasma Gondii Infection In Vitro - Lucia Tri Suwanti (Journal of Global Pharma Technology, 2016)
Toxoplasmosis is one zoonotic disease which caused by an obligate intracellular protrozoan parasite,  Toxoplasma gondii. The parasite infects humans and warm-blooded animals (mammals and birds). The drug of choice against toxoplasmosis is combination between pyrimethamin with sulfadiazine, but both can induce side effects and toxic to host cell, so alternative therapeutic compounds are needed.  Many reseachers have explored microalgae for food and medicine. One of the main components of  Spirulina platensis that plays a role in enhanching immunity is polysaccharides. The present study investigated effect of Spirulina polysaccharides on Toxoplasma gondii infection in Vitro. Polysaccharides of S. platensis were extracted with hot water and alkhaline method. Extraction Rate (ER), sugar and protein levels were compared between the two methods. The Hepatocyte Cells Line (HCL) were infected with T. gondii and treated with polysaccharides of S. platensis. The parameters were Parasite burden and Viability Host Cell. The result shows that Extraction Rate, carbohydrate and protein levels were affected by extraction method. Carbohydrate level in polysaccharides with hot water extraction was higher than alkhaline extraction, on the contrary, ER and protein level were lower. Polysaccharides of S. platensis did not protect HCL infected with T. gondii. More than 5 mg/mL polysaccharides of S. platensis was toxic to host HCL.  Keywords: Alkaline extraction, Hot water extraction, Polysaccharides, Spirulina platensis, Toxoplasma gondii.